Effects of creep feeding and post-weaning ration on calf performance - J.H. Warren; E.F. Smith; R.R. Schalles; L. Berger; G. Fink (Kansas Agricultural Experiment Station Research Reports, 1975)
We found no advantage for creep feeding calves for either all summer or 37 days prior to weaning. All calves were with their dams on native pasture. Calves not creep fed or creep fed only 37 days before weaning were sick less after weaning than those creep fed all summer. Rate of gain for 21 days after weaning was as good on a low energy weaning ration as on a high energy ration. However, more sickness occurred on the low energy ration.
Keywords: Cattlemen' s Day; 1975; Report of progress (Kansas State University. Agricultural Experiment Station); 230; Beef; Creep feeding; Calf performance; Weaning; Ration